Careers in focus: Travel & Hospitality / Ferguson Publishing - Ferguson Publishing
"Profiles jobs in travel and hospitality such as Baggage porters and bellhops, Bed and breakfast owners, Hotel concierges, Interpreters and translators, Ski resort workers, and Travel agents."--Résumé de l'éditeur.